Analysis of Learning Commitment and Learning Discipline with Student Learning Achievement at State Vocational School 1 Tomohon - Djubir R. E. Kembuan (JR Education, 2026)
This study aims to analyze the influence of learning commitment and learning discipline on student achievement at SMK Negeri 1 Tomohon in the context of vocational education. The study uses a quantitative approach with a correlational design through regression analysis to test the causal relationship between variables. The research variables consist of learning commitment and learning discipline as independent variables, and student learning achievement as the dependent variable. Data were collected using a Likert scale questionnaire that has been tested for validity and reliability, while learning achievement data were obtained through documentation of student academic grades. Data analysis was carried out using descriptive and inferential statistics through normality tests, linearity tests, regression significance tests, and path coefficient analysis. The results showed that learning commitment has a direct positive and significant effect on student learning achievement with a path coefficient value of ρy1 = 0.265 and tcount = 2.039 > ttable = 1.66 at a significance level of α = 0.05. In addition, learning discipline was also proven to have a positive and more dominant direct influence on student learning achievement with a path coefficient value of ρy2 = 0.491 and thitung = 7.290 > ttabel = 1.66. These findings indicate that the improvement in learning achievement of vocational high school students is not only influenced by academic ability, but also by learning engagement, behavioral consistency, self-control, and adherence to the learning process. In the context of technical and vocational education, learning commitment and learning discipline are strategic factors in shaping work readiness, professional responsibility, and the quality of graduates who are adaptive to the needs of the industrial world. This study provides theoretical contributions to the development of vocational education studies as well as practical implications for strengthening learning culture and character-based learning strategies in vocational high schools.